Recovering the Third World Force: World Christianity and Self-Determination - Chung, Soojin (2025)
While the current field of World Christianity serves as a necessary antidote to Eurocentric theological discourse, there remain significant opportunities for growth. In this article, I argue that the initial Third World influence behind the development of the field has diminished in current scholarship. 1 Third World theologians from Asia, Africa and Latin America who shaped the movement are not sufficiently recognised in contemporary World Christianity discourse. By focusing on the early development of the field, this article illuminates how pioneering scholars such as Gerald H. Anderson and Andrew Walls prioritised voices from the Global South instead of depending on secondary sources or re-narrating the stories of indigenous Christianity from a Western viewpoint. Finally, the article uses Ethnic Studies as a case study of self-determination. As defined by Ethnic Studies scholars, ‘self-determination’ refers to individuals’ and communities’ having the right to make their own choices and control their narratives and resources. World Christianity scholarship must critically engage with primary sources, whether through archives, oral histories or ethnography. In essence, Christianity in Asia, Africa and Latin America must be conveyed through its believers’ voices and self-determination.
Keywords: Gerald H. Anderson; Ethnic Studies; Self-determination; Third World theology; World Christianity